2021
DOI: 10.1186/s12920-021-00966-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and DNA methylation analyses suggest that two immune related genes are prognostic factors of colorectal cancer

Abstract: Background Colorectal cancer (CRC) is the second most prevalent cancer, as it accounts for approximately 10% of all annually diagnosed cancers. Studies have indicated that DNA methylation is involved in cancer genesis. The purpose of this study was to investigate the relationships among DNA methylation, gene expression and the tumor-immune microenvironment of CRC, and finally, to identify potential key genes related to immune cell infiltration in CRC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Among these SFs, HSPA1A and FAM50B were associated with OS in CRC. We found that patients with lower HSPA1A expression levels had higher OS rates, which was consistent with previous studies ( Xing et al, 2021 ). As a member of the heat shock proteins (HSPs) family, heat shock protein family A (Hsp70) member 1A (HSPA1A) exerted cytoprotective and immunological functions ( Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Among these SFs, HSPA1A and FAM50B were associated with OS in CRC. We found that patients with lower HSPA1A expression levels had higher OS rates, which was consistent with previous studies ( Xing et al, 2021 ). As a member of the heat shock proteins (HSPs) family, heat shock protein family A (Hsp70) member 1A (HSPA1A) exerted cytoprotective and immunological functions ( Wang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Among these splicing factors, HSPA1A and FAM50B were associated with OS in CRC. We found that patients with higher HSPA1A expression had reduced OS rates, consistent with previous study (Xing et al 2021). As a member of the heat shock proteins (HSPs) family, heat shock protein family A (Hsp70) member 1A (HSPA1A) exerted cytoprotective and immunological functions (Schmitt et al 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies indicated that OS-related genes could be used to construct the risk assessment model. According to previous studies, we also constructed a risk assessment model by using those three IR-DELs (C17orf77, GATA2-AS1, and TPT1-AS1) (18,19). The correlation analysis results showed that risk value was correlated with pathologic N, pathologic M, pathologic stage, several immune cells, and immune factors.…”
Section: Discussionmentioning
confidence: 99%
“…The risk model was established based on the expression data and multiplied Cox regression coefficients. The formula was set as followed, risk score = expression level of C17orf77 * (−1.5905) + expression levels of GATA2-AS1 * (−1.3003) + expression level of TPT1-AS1 * (−1.4072) (18,19). To further investigate the relevance of the risk model with the clinical pathological features of READ, we analyzed the relationship between the risk value and vital status, gender, pathologic NMT, and pathologic stage.…”
Section: Construction Of Specific Risk Assessment Modelmentioning
confidence: 99%